PRARANCANGAN PABRIK ETILEN OKSIDA DARI ETILEN DENGAN PROSES OKSIDASI KAPASITAS 150.000 TON/TAHUN - Ismail, Andy; Hamid Abdillah,, S.T., M.T; Emi Erawati,, S.T,. M.Eng (2016)
Pre-draft Factory ethylene oxide oxidation process with capacity of 150,000 tons / year in operation for 330 days per year. Factory will be established in the industrial area Cilegon, Banten with 9.705 m2 land area and 124 employees. The raw material ethylene form PT. Chandra Asri Petrochemical, Cilegon and Oxygen from PT. Air Liquide Indonesia, Cilegon. Making the reaction of ethylene oxide oxidation process using fixed bed multitube reactor with silver catalysts. On phase gases, irreversible, with exothermic temperature from 220 to 252.6°C and pressure 15 atm. The resulting product side carbon dioxide and air. Raw materials production of ethylene oxide needs ethylene amounted 117.990 tons / year and oxygen amounted to 74.914 tons / year. Process supporting utilities include the air supply unit amounted to 108.3 m3 / day, steam unit amounted to 536.7 m3 / day be produced from boiler with diesel fuel used to 117.9 ft3 / hour, unit power needs power of 1263.68 kWh be produced from PLN, and waste treatment unit. The result of the economic ethylene oxide using fixed capital Rp. 314 644 880 961. Advantages per year before tax Rp 2,478,140,104,505, profit per year after tax Rp 1,982,512,083,604, Return of Investment (ROI) after tax 49.9% and 39.1%, Pay Out Time (POT) before tax 1.72 years and after tax of 2.08. Economic analysis with Break Even Point and Shut Down Point 53% and 42%. So plant can be established because Pay Out Time and after 2.08 years.